2000
DOI: 10.1007/bf03185795
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ring pack lubrication

Abstract: This paper describes a method developed for the simulation of ring pack lubrication characteristic in an internal combustion engine. In general, the quantity of oil supply for piston ring lubrication may be insufficient in filling the entire volume formed at the interference between the piston ring and the cylinder liner. Thus the oil starvation condition should be considered in analyzing piston ring lubrication. In order to reasonably estimate the amount of oil left over on the cylinder liner, the flow rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It can be concluded that for some crank angles, insufficient oil is being supplied to the ring face for fully flooded conditions to occur, so appropriate boundary conditions are of prime importance. Lee and Han 39 applied a piston-ring lubrication model that considers starvation to evaluate the amount of oil supplied to the ring–liner interface based on lubrication theory and oil flow continuity algorithm using open-end boundary conditions. The results show that the compression rings in the ring-pack operate under starvation for most crank angles and effective ring width was reduced by 20–30%.…”
Section: Lubrication Mechanismsmentioning
confidence: 99%
“…It can be concluded that for some crank angles, insufficient oil is being supplied to the ring face for fully flooded conditions to occur, so appropriate boundary conditions are of prime importance. Lee and Han 39 applied a piston-ring lubrication model that considers starvation to evaluate the amount of oil supplied to the ring–liner interface based on lubrication theory and oil flow continuity algorithm using open-end boundary conditions. The results show that the compression rings in the ring-pack operate under starvation for most crank angles and effective ring width was reduced by 20–30%.…”
Section: Lubrication Mechanismsmentioning
confidence: 99%
“…Considering rather complicated configurations of T and L-type joints, we prepared an auto-mesh generation program for combined shell/line-spring modeling [19]. Tension, bending and internal pressure loadings can be defined in various ways for T and L-type joints due to rather complicated configurations.…”
Section: Analyses Of Pipe-joints With Semi-elliptical Surface Cracksmentioning
confidence: 99%
“…However in the case of the existing pin-type load cell, the measuring range is very narrow. Therefore it is necessary to develop a many-angular pin type load cell in order to measure the load in wide range [2,3].…”
Section: Introductionmentioning
confidence: 99%